P074 Human amnion epithelial cells reduce intestinal inflammation in a dextran sulfate sodium-induced murine model of acute colitis. (16th January 2018) - Kuk, N; Correia, J; Alhomrani, M; Lim, R; Sievert, W; Hodge, A; Moore, G
Abstract: Background: Inflammatory bowel disease encompasses a group of conditions characterised by inflammation and ulceration of the colon resulting in diarrhoea, haematochezia and weight loss. This often requires hospitalisation, corticosteroids and long-term immunosuppressants. However, these treatments are associated with numerous side effects and a subset of patients remain refractory to treatment. Stem cells, such as the pluripotent human amnion epithelial cells (hAECs), have been explored as a potential therapy. Ethically sourced from placentas, hAECs possess anti-inflammatory properties and no known safety issues. We examined the efficacy of hAECs in a dextran sulfate sodium (DSS) induced murine model of acute colitis. Methods: C57BL/6J mice received 2% DSS (w/v) in their normal drinking water for 7 days. At Day 2, Group 1 ( n = 17) received a tail vein of 2 × 10 6 hAECs. At Day 4, Group 2 ( n = 17) received an injection of 2 × 10 6 hAECs. DSS control mice ( n = 17) were untreated. Mice were monitored daily and culled at Day 8. Colitis severity was scored histologically using H&E stained colon sections. Colonic neutrophil infiltration was determined by myeloperoxidase (MPO) activity assay. IL-1β, TNF-α, IL-6, IFN-γ and IL-10 were measured through enzyme-linked immunosorbent assays. Colon sections were stained with anti-F/480 antibody to identify macrophages. Results: Untreated DSS mice lost significantly more body weight (−17.4%) compared with hAEC treated mice (Group 1: −5.6% ( p < 0.0001), Group 2: −8.8% ( p < 0.0001)). Treatment prevented colon shortening in Group 1 (6.7 cm p < 0.001) and Group 2 (6.3 cm, p < 0.01) compared with controls (5.3 cm). Similarly, hAEC treated mice had significantly lower histological severity scores (Group 1: p < 0.0001, Group 2: p < 0.001). MPO activity was almost halved in Groups 1 ( p < 0.0001) and 2 ( p < 0.0001). Treatment also significantly reduced concentrations of pro-inflammatory cytokines (IL-1β, TNF-α, IL-6, IFN-γ) whilst up-regulating the anti-inflammatory cytokine IL-10. hAEC treatment significantly reduced intestinal macrophages at Day 2 ( p < 0.01) but not Day 4. Apart from a lower histological severity score in Group 1, there were no others differences comparing Group 1 and 2. Conclusions: hAECs exert a protective effect in colitis and reduce the severity of disease, by reducing the level of neutrophil and macrophage infiltration into the colon and decreasing concentrations of pro-inflammatory cytokines and increasing anti-inflammatory cytokine. The therapeutic potential of hAECs in IBD is promising and further research into their optimal delivery and mechanisms of action is warranted.